LITURGI YANG BERGERAK: KOREOGRAFI ROHANI DALAM IBADAH PUJIAN ALA DAUD - Kilat Kasanang (Diegesis : Jurnal Teologi, 2025)
This study examines the profound role of bodily movement and choreography in Christian worship, advocating for its reintegration as an essential liturgical dimension, inspired by the Davidic model. It introduces "Kinetic Theology" as a new theological framework systematically affirming the intrinsic spiritual significance of the body in worship, and "Spiritual Choreography" as its practical manifestation. By analyzing biblical precedents, tracing historical shifts, and addressing contemporary challenges, this study challenges traditional mind-body dualism in worship, proposing that intentional movement can serve as a powerful prophetic and restorative form of praise, fostering a more holistic and deeply engaged liturgical experience.